CONTEMPORARY EDUCATION IN AUSTRALIA: WELLBEING EDUCATION AT BALCOMBE GRAMMAR SCHOOL MOUNT MARTHA VICTORIA - Lis Safitri (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2020)
Abstract:Australian schools paid a great attention to the students’ wellbeing at school. This study aimed to explain wellbeing education in Australia with Balcombe Grammar School as a sample of the study. This research was qualitative research using descriptive method. The primary data had been collected through interview, documentation, and observation at Balcombe Grammar School (BGS) Mount Martha, Victoria in 2017. The data had been analyzed using Miles and Huberman framework. The result showed that wellbeing education in Australia was instructed by the Australian Government, organized by the school, and helped by independent institutions named KidsMatter, MindMatters, and CASEL. Balcombe Grammar School had some programs on wellbeing education, such as the golden time, circle time, faith and wellbeing classes, pastoral care classes, and health classes. These programs were not only conducted as part of BGS curriculum but also integrated into the teaching instruction in all of the subjects and daily life at school.Abstrak:Sekolah-sekolah di Australia telah memberikan perhatian yang cukup besar terhadap pendidikan wellbeing para siswa. Penelitian ini bertujuan untuk menjelaskan pendidikan wellbeing di Australia dengan mengambil Balcombe Grammar School sebagai sampel penelitian. Penelitian ini merupakan penelitian kualitatif dengan menggunakan metode deskriptif. Pengumpulan data dilaksanakan dengan metode wawancara, dokumentasi, dan observasi di Balcombe Grammar School (BGS) Mount Martha, Victoria pada tahun 2017. Data dianalisis dengan model analisis Miles dan Huberman. Hasil penelitian menunjukkan bahwa pendidikan wellbeing di Australia diatur oleh Pemerintah Federal Australia, dijalankan oleh masing-masing sekolah, dan dibantu oleh lembaga independen yang bernama KidsMatter, MindMatters, dan CASEL. Balcommbe Grammar School memiliki beberapa program dalam mengembangkan pendidikan wellbeing di sekolah, misalnya golden time, circle time, faith and wellbeing classes, pastoral care classes, dan health classes. Program-program tersebut tidak berjalan secara parsial melainkan terintegrasi di kelas dalam pelajaran lain serta dalam kehidupan keseharian selama jam sekolah berlangsung.